Performanz und Imagination in der Oralkultur Südosteuropas - Puchner, Walter (Böhlau, 2017)
This monograpy analyses forms of performativity in the oral cultures of Southeast-Europe, as gestures, masks and disguising, theatrical customs, popular and professional theatre, as well as forms of imagination, like superstitions, magic practices, popular religion, demonology, etc.